Development of a Palm Nut Cracker with Spinning Disc Shell Separator. - Lukman, B. O.; Oyegbile, S. O.; Adeshina, O. M.; Owoo, E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
This paper presents the design and evaluation of a palm nut cracker with a spinning disc separator. The machine has five units namely: the hopper, the cracking chamber, the separating unit made of a vibrating screen and a spinning disc, the collectors, and the drive unit. The machine was designed and fabricated using locally sourced materials, and it was tested and evaluated at two operating speeds (480 and 660rpm) with palm nuts at three moisture contents of 5, 10, and 12%, respectively. The kernel-shell mixture was separated using the spinning disc made of three different materials; mild steel, plywood, and jute fiber. At a constant feed rate of 50 nuts per second, the cracking unit achieved a maximum cracking efficiency of 94.52%, while the throughput capacity was 8.05 kg/hr at 660 rpm for nuts with a moisture content of 10%. The spinning disc constructed of mild steel had the highest separation efficiency of 69.2% and kernel purity of 90.69% for cracked mixture with 12% moisture content at 60 rpm.